2005
DOI: 10.1055/s-2004-837265
|View full text |Cite
|
Sign up to set email alerts
|

Premature Infants Are Less Capable of Maintaining Thermal Balance of Head and Body with Increases of Thermal Environment than with Decreases

Abstract: We investigated whether premature infants nursed at the upper range of normal body temperature are more capable of maintaining their nasopharyngeal and rectal temperature when exposed to a 1 degrees C increase or a 1 degrees C decrease of incubator temperature. In a randomized controlled trial, premature infants were exposed to a 1 degrees C increase (T + 1 degrees C; n = 10), or to a 1 degrees C decrease (T - 1 degrees C; n = 10) of incubator temperature. Nasopharyngeal, rectal, and skin temperatures as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Intraischemia cooling contributed to profound protection in the cortex, and this protection was correlated with down‐regulation of apoptosis‐related mechanisms and up‐regulation of the Akt survival signalling pathway. The prevailing routine in clinical practice to prioritize warming neonates in the resuscitation situation may be harmful to the brain (Simbruner et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Intraischemia cooling contributed to profound protection in the cortex, and this protection was correlated with down‐regulation of apoptosis‐related mechanisms and up‐regulation of the Akt survival signalling pathway. The prevailing routine in clinical practice to prioritize warming neonates in the resuscitation situation may be harmful to the brain (Simbruner et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Zero-heat-flux core temperature monitoring using a temperature probe covered by a piece of heat insulator is widely accepted as a reliable surrogate marker for invasive methods (Simbruner et al, 2005(Simbruner et al, , 1994van der Spek et al, 2009). Fox and Solman (1971) further improved this technique using a heater and a thermal flux transducer, the accuracy of which has been validated in a range of body locations and clinical situations in reference to jugular vein and other body core temperatures (Yamakage and Namiki, 2003;Kimberger et al, 2009;Akata et al, 2007;Ball et al, 1973).…”
Section: Non-invasive Monitoring Of Brain Temperaturementioning
confidence: 99%
“…Local heat production is represented by cerebral metabolism, whereas heat removal depends on cerebral blood flow (CBF) and heat dissipation through the scalp (Sukstanskii and Yablonskiy, 2006). Previous pre‐clinical and clinical studies have identified factors that determine body/brain temperature in newborn infants, such as ambient temperature and humidity, and maturity and body size (Karlsson et al, 1995; Simbruner et al, 2005; Iwata et al, 2006). However, associations between brain temperature, metabolism, and perfusion have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…23 With this on-off control, there is an overshoot and undershoot in the air temperature. 2,16,18,[21][22][23][24] Skin control often leads to large fluctuations in air temperature. 5,6,18 Air control leads to skin temperature fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…2,16,18,[21][22][23][24] Skin control often leads to large fluctuations in air temperature. 5,6,18 Air control leads to skin temperature fluctuations. Perlstein et al 17 observed that apnea in newborns was caused by thermal instability.…”
Section: Introductionmentioning
confidence: 99%